Determination of gas film mass transfer coefficient in a packed bed reactor for the catalytic combustion of hydrogen. (20th July 2019) - Sandeep, K.C.; Mohan, Sadhana; Mandal, D.; Mahajani, Sanjay
Graphical abstract: Highlights: The overall catalytic combustion kinetics of H2 in air is studied. Experimental data in low Peclet number region is generated ( Pe 1.4 - 14 ) . The mass transfer coefficients were estimated for different Re p (7–77). A correlation is developed in terms of Sh, Re p and S c for H2 -air system. Contribution of individual resistances was estimated at different Re p (7–77). Abstract: The overall kinetics of catalytic combustion of hydrogen in air is decided by the contribution of the different resistances offered in individual steps such as external diffusion, internal diffusion and surface reaction. To estimate the contribution of external mass transfer resistance, empirical correlations in terms of dimensionless numbers viz., Sherwood number, particle Reynold's number, and Schmidt number are used in general. The Schmidt number for hydrogen in air is approximately 0.2 and most of the mass transfer correlations in packed bed reactors are valid for Schmidt number higher than 0.6, which corresponds to that of water vapour in the air. The external mass transfer correlations applicable for hydrogen-air system are scarce. In the present study, the external mass transfer effects were decoupled from internal diffusion and intrinsic reaction by conducting experiments with different particle Reynolds numbers in a packed bed batch reactor with complete recycle. Further, the system is theoretically modeled and the external film mass transfer coefficients were estimated at different particle Reynold's numbers using experimental data. Based on the experimental data, a new mass transfer correlation has been proposed to determine the gas film mass transfer coefficient of hydrogen in the air in packed bed reactors, in terms of conventional dimensionless numbers i.e., Sherwood number, Schmidt number, and particle Reynolds number. Further, the contribution of external mass transfer resistance on the overall reaction kinetics was also estimated.